Cassirer - Matherne, Samantha (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Ernst Cassirer (1874-1945) occupies a unique place in twentieth-century philosophy. His view that human beings are not rational but symbolic animals and his famous dispute with Martin Heidegger at Davos in 1929 are compelling alternatives to the deadlock between 'analytic' and 'continental' approaches to philosophy. An astonishing polymath, Cassirer's work pays equal attention to mathematics and natural science but also art, language, myth, religion, technology and history. However, until now the importance of his work has largely been overlooked. In this outstanding introduction Samantha Matherne examines and assesses the full span of Cassirer's work. Beginning with an overview of his life and works she covers the following important topics
Cassirer's life and works -- The neo-Kantian framework -- Philosophy of mathematics -- Philosophy of natural science -- Philosophy of culture as the philosophy of symbolic forms -- The individual symbolic forms, part I: from myth to natural science -- The individual symbolic forms, part II: the ethics and politics of culture -- Cassirer's legacy.
OCLC-licensed vendor bibliographic record.
Keywords: Cassirer, Ernst, -- 1874-1945.; PHILOSOPHY / General